Relationship between Knowledge and Stigma with Attitude Towards People with Leprosy in Professional Nursing Students - Ishomatul Faizah; Laily Hidayati; Ika Nur Pratiwi (Institute of Topical Disease Universitas Airlangga, 2024)
The bacteria Mycobacterium leprae is the source of the chronic infectious illness leprosy (M. leprae). In society, leprosy still carries a shame. The erroneous impression of leprosy gives birth to stigma. Leprosy is thought to be brought on by curses, witchcraft, divine retribution, sin, or genetics. A person's perception of leprosy and lack of understanding about it might have an impact on how they feel about those who have it. Even among health students, information alone will not be sufficient to end the stigma against those who have leprosy; also, students need to learn how to develop greater empathy for those who have the disease. This study sought to ascertain the association between leprosy knowledge and stigma and attitudes among nursing students at the professional level. In this study, a cross-sectional methodology is used with a descriptive correlational design. A total 320 professional nursing students participated in the survey. Total sampling was used to select respondents based on inclusion and exclusion criteria. Utilizing the SPSS version 21, data were gathered by questionnaire and analyzed using the Spearman's rho test at a significance level of 0.05. The Spearman's rho test results revealed a positive link between attitude and knowledge (p=0.001), but a negative relationship between attitude and stigma (p=0.000). It was determined that attitudes toward people with leprosy were significantly influenced by information, stigma, and those attitudes. The better the mindset, the more one knows about leprosy. Leprosy patients are treated better when there is less stigma associated with their condition.